2019
DOI: 10.1007/s11764-019-00747-z
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity exercise during chemotherapy induces beneficial effects 12 months into breast cancer survivorship

Abstract: Purpose Whether the benefits of exercise during chemotherapy continue into survivorship is not well-known. Here, the aim was to examine the effects of two exercise interventions on self-reported health-related and objectively measured physiological outcomes 12 months following commencement of chemotherapy. Methods Two hundred and forty women with breast cancer stage I–IIIa were randomized to 16 weeks of high-intensity aerobic interval training combined with either resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(155 citation statements)
references
References 45 publications
9
134
0
12
Order By: Relevance
“…Our moderator analysis suggests that both continuous and interval aerobic training are effective at increasing VO 2max . There is some compelling evidence that vigorous intensity continuous aerobic training performed during chemotherapy counteracts cancer-related fatigue, which can last up to 12 months after treatment completion, and reduces the time to return to work as compared with the UC group [ 57 ]. However, we acknowledge that performing continuous aerobic training at vigorous intensities is very demanding and may not be feasible for women with BC undergoing chemotherapy, thus interval training should be considered as a viable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Our moderator analysis suggests that both continuous and interval aerobic training are effective at increasing VO 2max . There is some compelling evidence that vigorous intensity continuous aerobic training performed during chemotherapy counteracts cancer-related fatigue, which can last up to 12 months after treatment completion, and reduces the time to return to work as compared with the UC group [ 57 ]. However, we acknowledge that performing continuous aerobic training at vigorous intensities is very demanding and may not be feasible for women with BC undergoing chemotherapy, thus interval training should be considered as a viable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant therapy strategies have been shown to improve resectability of previously inoperable cancers by reducing the complexity of operations, e.g., by successfully diminishing tumor tissue [14]. However, prehabilitation programs are also targeting non-surgical cancer patients receiving pharmacological treatment only, e.g., as chemotherapy and/or radiotherapy [15][16][17]. In this context, a recent meta-analysis on 3257 patients with cancer indicated that moderate aerobic exercise performed at 70-80% of maximum heart rate not only was feasible and safe but also showed beneficial effects in QoL and physical functioning and maintained or at least improved fitness during concomitant chemotherapy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the RT‐HIIT intervention had larger effect sizes on patient‐reported symptoms, especially multidimensional cancer‐related fatigue and preservation of cognitive functioning compared with the AT‐HIIT group . These positive effects on total symptoms, cancer‐related fatigue and strength persisted at 1 and 2 years after chemotherapy relative to the usual care group despite no current differences between groups in objectively measured physical activity . Taken together, these results demonstrate that the combination of aerobic interval training and resistance training twice per week for 16 weeks throughout chemotherapy treatment improves the patient experience of chemotherapy, prevents negative physiological sequelae of chemotherapy, and improves long‐term patient well‐being.…”
mentioning
confidence: 70%